Hydroxylysine glycosides of corneal collagen - Ibrahim, J; Ibrahim, Jamal (1986)
The universally found thin and uniform features of collagen fibrils constituting the corneal stroma (Craig and Parry, 1981), are essential for corneal transparency (Goldman et at., 1968). Corneal collagen contains more hydroxylysine glycoside than most collagens. In relation to the 'D stagger' arrangement of collagen molecules in the fibril, it was postulated that an excess of hydroxylysine - glycoside occurring in the 'overlap' region may limit fibril growth in the lateral direction by steric hindrance (Morgan et al., 1970). The ultimate aim of this work was to pinpoint the sites of hydroxylysine-glycosides in the corneal collagen molecule, bearing in mind their location with respect to the fibril gap/overlap structure. Determination of hydroxylysine-glycosides were carried out on an automated amino acid analyser with the much reduced total analysis time of 1¼ hours per sample, using a two - buffer elution system developed during this work. Cyanogen bromide peptides αl CBS, αl CB7 and αl CBS were isolated and shown to contain 1.0, 0.97 and 1.21 residues of hydroxylysine-glycoside respectively per peptide. It was also proven beyond doubt that peptide αl CBS has a higher electrophoretic mobility on SDS gels than peptide αl CB7, pointing to mistakes found in the literature. In the 271 residue peptide αl CB7, analysis of tryptic and V8 - protease peptides led to the discovery of seven glycoside sites, the major site being at lysyl position 684 (numbers from start of αl[I] helical sequence). This lysyl position was found to be 46% hydroxylysine-glycoside, being 34% glucosylgalactosyl- hydroxylysine and 12% galactosylhydroxylysine. Of position 564, 17% was hydroxylysine-glycoside while of the other positions 573, 603, 648, 657 and 756, between 5% and 12% was hydroxylysine glycoside. In relation to the fibril gap/overlap structure, position 756 is in an overlap zone and position 564 is just inside one. Positions 573 and 684 are just inside a gap zone which also contains the other glycoside sites. Another possible site at position 729 was not found to contain hydroxylysine nor therefore, any glycoside. These findings are discussed with respect to the possible role of hydroxylysine glycosides in limiting collagen fibril diameter. Comparisons of the amino acid sequences around the seven glycoside sites however gave no clues as to what makes some lysyl residues more susceptible to modification than others. The possible reasons for the high extent of lysyl modification in the cornea are also discussed.